Oxidative stress profiles in brain point out a higher susceptibility of fish to waterborne divalent mercury compared to dietary organic mercury - Cardoso, O (2017)
This study examines, for the first time, the neurotoxicity of Hg(II) and MeHg in fish (Diplodus sargus) in a time-course comparative perspective and considering realistic exposure levels and routes. Both forms followed an identical time-variation pattern of accumulation in the brain, but dietary MeHg was more efficiently transported to the brain. MeHg was substantially eliminated from the brain in 28 days of depuration, which did not occur for Hg(II). Moreover, Hg(II) displayed a high neurotoxicity potential, as unveiled by the poor activation of brain antioxidant defenses and recurrent oxidative damage (as protein oxidation), while the opposite was recorded upon MeHg exposure. These results highlight the need to include Hg(II) in future environmental health assessment plans, preventing an underestimation of the risk for wild fish populations, which has probably been occurring due to the long-standing idea of the higher toxicity of MeHg in comparison with inorganic Hg forms.